PERCEPTIONS OF CIVIL AND MILITARY HEALTH AGENCIES IN KUALA LUMPUR, MALAYSIA ON HEALTH NEEDS ASSESSMENT DURING URBAN DISASTER RESPONSE - Mohd Rashidi Abdul Salam; Nurhan Norris Ma; Aida Jaffar; Badrul Hisham Abd Samad; Ambigga Krishnapillai; Norhazlina Fairuz Musa Kutty (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Introduction: Health needs assessment (HNA) following a disaster is a systematic method to review the health issues facing the population affected by the disaster. It leads to an agreed priorities and appropriate resource allocation that will improve the victim’s health. For HNA to be accurate, it must be deployed within days or even hours after the disaster as the health response team initially using their resources in the search and rescue (SAR) efforts, will start to shift their health response to all victims of the disaster. Objectives: The understanding of HNA among health agencies involved in managing urban disasters, their experience, challenges and suggestions for improvement. Methods: A qualitative research methodology with single case study design was utilized to explore HNA during disaster which included in-depth interview (IDI) with representatives from the Malaysian Ministry of Health (MOH) and the health services of the Malaysian Armed Forces (MAF) in Kuala Lumpur, Malaysia. Data were analysed using ATLAS.ti v23 software. Results: The IDI with MOH and MAF health services representatives highlighted a very good understanding of HNA post urban disasters even though MOH had limited protocols in doing so. However, the MAF representative highlighted that one of the reasons HNA was not done is, due to the multiple structure of commands that complicates the management during disasters. Both the civilian and military health agencies had very good understanding and vast experience in post disaster health management even without performing a proper HNA. Limitation: This study did not involve any Non Goverment Organizations (NGOs) and community groups who are actively involved in health response during urban disasters. Conclusion: The challenges faced during past disasters has shown the importance of HNA in managing health of the affected population post disasters and should be recommended by the relevant authorities.